Forecasting Pemakaian dan Pengadaan Bahan Material Proyek Marka Jalan dengan Metode Exponential Smoothing - Simbolon, Nomi Putri S (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
The benefits of existing data to advance the activities in decision-making is not enough just relying on operating data only, required a data analysis to explore the potential of existing information. one data mining technique that can be done that is forecasting. This study to forecast the use of road marking project materials at PT. Jonathan uses the Exponential Smoothing method. Exponential Smoothing method searched for random alpha values ​​to find alpha that has a minimal error calculated with Means Absolute Percentage Error (MAPE). Then the results of forecasting that has alpha with minimal error value set as a result of forecasting for the next period. The results of forecasting analysis of the use of raw material material for the period of 2017 is set to use alpha value 0.1 can forecasting results worth 1278 with MAPE error value of 5.0419%. While forecasting results for material materials so using alpha 0.3 can forecasting results of 827 with MAPE error value of 4.8099%.